2009
DOI: 10.1007/s10637-009-9259-z
|View full text |Cite
|
Sign up to set email alerts
|

MMPT: a thiazolidin compound inhibits the growth of lung cancer H1792 cells via Fas-mediated and caspase-dependent apoptosis pathway

Abstract: MMPT, a thiazolidin compound, was identified in our laboratory as a novel antineoplastic agent with a broad spectrum of antitumor activity against many human cancer cells. However, the related mechanism has yet not been revealed. In this study, we investigated the cellular and molecular events underlying the antitumor function of this compound in human lung adenocarcinoma H1792 cells, focusing on the early cytotoxic effect. Treatment of H1792 cancer cells with MMPT (0.1-100 microM for 24-72 h) resulted in a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Also one should mention that when comparing the GI 50 values on each cancer cell line for 3f there is some correlation with rhizoxin as inhibitor of tubulin (NSC:S332598 Endpt:GI50 ExpId:AVGDATA hiConc: −5.3) p=0.686. It is interesting that among the possible ways of “hit-compounds” antitumor effect realization COMPARE analysis does not deny the possible induction of apoptosis, which is an argument for the experimental confirmation of this hypothesis considering the anticancer mechanism of action of structurally related 5-(4-methylbenzylidene)-2-phenylamino-1,3-thiazolidin-4-one (MMPT) [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Also one should mention that when comparing the GI 50 values on each cancer cell line for 3f there is some correlation with rhizoxin as inhibitor of tubulin (NSC:S332598 Endpt:GI50 ExpId:AVGDATA hiConc: −5.3) p=0.686. It is interesting that among the possible ways of “hit-compounds” antitumor effect realization COMPARE analysis does not deny the possible induction of apoptosis, which is an argument for the experimental confirmation of this hypothesis considering the anticancer mechanism of action of structurally related 5-(4-methylbenzylidene)-2-phenylamino-1,3-thiazolidin-4-one (MMPT) [27]. …”
Section: Resultsmentioning
confidence: 99%
“…MMPT-induced apoptosis in treated cells through a membrane-mediated mechanism was supported by the up-regulated expression of Fas (CD95/APO-1), and Fas ligand. The overall study demonstrated, MMPT-induced growth inhibition of H1792 cells through a Fas-mediated and caspasedependent apoptosis pathway, which suggested that MMPT might be used as a Fas/FasL and caspases promoter to initiate lung cancer cell apoptosis [72]. In the development of certain types of solid tumors, EGFR tyrosine kinase is reported to play an important role, particularly because it is an attractive target for breast cancer [73] (Including TNBCs and HER2-negative breast cancer).…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 86%
“…The overall study proposed compound 18 (MMPT) as the selective anti-cancer agent which retained efficacy against the P-glycoprotein-negative as well as positive cancer cells [71]. Continuing a study on MMPT, Zhao et al [72] evaluated its antineoplastic activity against a lung cancer cell line (H1792) at different concentrations (0.1-100 μM) for a period of 24-72 h. In the MTT assay, compound MMPT exhibited growth inhibition in a time-dependent as well as dose-dependent manner. This effect was accompanied by apoptosis, evident by Nucleosome ELISA, H33258 stained assay, and Sub-G1 analysis.…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 99%